Trait Association and Path Analysis Studies for Yield Traits in Recombinant Inbred Lines Derived from Cross KP×A-69-1 in Rice (Oryza sativa L.) - Snehi, Sanchika; Pandey, Prachi; Rathi, S. R.; Pallavi; Singh, P. K.; Upadhyay, Sameer (International Journal of Bio-resource and Stress Management, 2022)
Studies pertaining to genetic variability, trait association and correlation among yield traits give elementary idea about the amount and direction of genetic association of the traits in the population and devising appropriate breeding methods for further improvement of the crop. This study aimed to estimate coefficients of variability, genetic advance, heritability, trait association and path coefficient analysis among 40 recombinant inbred lines (F7) derived from biparental cross (KP×A-69-1). These lines were evaluated for yield and its contributing traits in randomised complete block design (RCBD) during kharif-2018. High estimates of Genotypic Coefficient of Variations (GCV) and Phenotypic Coefficient of Variations (PCV) were observed for filled grain panicle-1 followed by total grain panicle-1, number of effective tillers plant-1, panicle weight and grain yield plant-1. High heritability conjugated with high genetic advance were recorded for plant height and filled grains panicle-1. Panicle weight, filled grain panicle-1, number of effective tillers plant-1 and panicle length showed positive and significant (p≤ 0.01) correlation with grain yield plant-1. Path coefficient analysis showed that despite significant and positive correlation of grain yield plant-1 with many variables only correlation of panicle weight and number of effective tillers plant-1 were verified to have relationship of cause and effect. Overall result gesture towards role of panicle weight, number of effective tillers plant-1 and filled grains panicle-1 as important variables for use in grain yield plant-1 assessment programs as selection indices.